1995
DOI: 10.1152/jappl.1995.79.3.838
|View full text |Cite
|
Sign up to set email alerts
|

Slow component of O2 uptake during heavy exercise: adaptation to endurance training

Abstract: Seven untrained male subjects [age 25.6 +/- 1.5 (SE) yr, peak O2 uptake (VO2) 3.20 +/- 0.19 l/min] trained on a cycle ergometer 4 days/wk for 6 wk, with the absolute training workload held constant for the duration of training. Before and at the end of each week of training, the subjects performed 20 min of constant-power exercise at a power designed to elicit a pronounced slow component of VO2 (end-exercise VO2-VO2 at minute 3 of exercise) in the pretraining session. An additional 20-min exercise bout was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
3
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 31 publications
7
83
3
5
Order By: Relevance
“…Also, following six weeks of endurance training, Womack et al (1995) found an attenuated increase in  VO2 between 10 and 20 minutes of highintensity cycling exercise at the same absolute power. The reduced  VO2 slow component was also observed when plasma epinephrine concentrations were increased to pre-training levels in the post-training condition.…”
Section: Resultsmentioning
confidence: 82%
“…Also, following six weeks of endurance training, Womack et al (1995) found an attenuated increase in  VO2 between 10 and 20 minutes of highintensity cycling exercise at the same absolute power. The reduced  VO2 slow component was also observed when plasma epinephrine concentrations were increased to pre-training levels in the post-training condition.…”
Section: Resultsmentioning
confidence: 82%
“…The SC is known to be reduced after endurance training 6,7 when exercising at the same pre-training work rate …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ratio of phosphate produced per oxygen consumed (P=O ratio) is 18% lower in isolated mitochondria from type II compared to type I muscle, which suggests uncoupling of mitochondrial respiration. 5 Endurance training between 2 and 8 weeks has been observed to reduce the size of the SC, 6,7 however it is unlikely that changes in muscle fibre distribution would have occurred during this period. 8,9 It is likely that factors either in addition to or other than muscle fibre type are contributing to the magnitude of the SC.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the muscle and blood lactate levels would be appreciably higher at the intensities used in the present study and consequently lactate related metabolic cost may be contributory and would persist in the off-transient. Other factors such as the cost of ventilation (Womack et al 1995), the influence of adrenaline (epinephrine) ) and muscle temperature (Koga et al 1997) have also been examined and essentially discarded as important contributors to the slow phase. We examined our data with respect to the gain component of ýOµ and work rate.…”
Section: Discussionmentioning
confidence: 99%